2019
DOI: 10.3389/fimmu.2019.01727
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Phosphodiesterases—Towards a Tailor-Made Approach in Multiple Sclerosis Treatment

Abstract: Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system (CNS) characterized by heterogeneous clinical symptoms including gradual muscle weakness, fatigue, and cognitive impairment. The disease course of MS can be classified into a relapsing-remitting (RR) phase defined by periods of neurological disabilities, and a progressive phase where neurological decline is persistent. Pathologically, MS is defined by a destructive immunological and neuro-degenerative interplay. Current tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 215 publications
0
53
0
1
Order By: Relevance
“…This review will focus on AKAP/cAMP complexes. Extensive research has demonstrated that elevating cAMP and cGMP levels can drive the CNS towards a neuroprotective environment to prevent damage 9 - 17 . Achieving this elevation is possible through the anabolic pathway via guanylyl cyclase (GC) or adenylyl cyclase (AC), or by blocking phosphodiesterases (PDEs), which hydrolyze and break down cGMP and cAMP.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review will focus on AKAP/cAMP complexes. Extensive research has demonstrated that elevating cAMP and cGMP levels can drive the CNS towards a neuroprotective environment to prevent damage 9 - 17 . Achieving this elevation is possible through the anabolic pathway via guanylyl cyclase (GC) or adenylyl cyclase (AC), or by blocking phosphodiesterases (PDEs), which hydrolyze and break down cGMP and cAMP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the modulation of neuroplasticity effects, cyclic nucleotides also affect neuroinflammatory processes 14 , 66 . Through compartmentalization of signaling cascades, generic cAMP and cGMP can selectively influence different processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…cAMP is the most studied second messenger in the context of T lymphocyte activation and proliferation [ 19 ]. It has been reported that the increase of cAMP level attenuates the T lymphocyte-mediated production of pro-inflammatory cytokines such as IFN-γ and interleukin (IL)-1b (IL-1b) suggesting that a decrease of cAMP level is required for T cell activation [ 14 , 20 , 21 ]. The activation of immune cells, especially T cells, is also related to OS [ 15 ] and the peripheral blood mononuclear cells (PBMCs) of MS patients show an impaired redox status associated with a metabolic reprogramming that includes mitochondrial alterations [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%